Crosstalk between Signaling Pathways Provided by Single and Multiple Protein Phosphorylation Sites. Issue 2 (30th January 2015) - Nishi, Hafumi; Demir, Emek; Panchenko, Anna R.
Abstract: Cellular fate depends on the spatiotemporal separation and integration of signaling processes that can be provided by phosphorylation events. In this study, we identify the crucial points in signaling crosstalk that can be triggered by discrete phosphorylation events on a single target protein. We integrated the data on individual human phosphosites with the evidence on their corresponding kinases, the functional consequences of phosphorylation on activity of the target protein and corresponding pathways. Our results show that there is a substantial fraction of phosphosites that can play critical roles in crosstalk between alternative and redundant pathways and regulatory outcome of phosphorylation can be linked to a type of phosphorylated residue. These regulatory phosphosites can serve as hubs in the signal flow and their functional roles are directly connected to their specific properties. Namely, phosphosites with similar regulatory functions are phosphorylated by the same kinases and participate in regulation of similar biochemical pathways. Such sites are more likely to cluster in sequence and space unlike sites with antagonistic outcomes of their phosphorylation on a target protein. In addition, we found that in silico phosphorylation of sites with similar functional consequences has comparable outcomes on a target protein stability. An important role of phosphorylation sites in biological crosstalk is evident from the analysis of their evolutionary conservation. Graphical abstract: Highlights: This study identified and provided the list of phosphosites that serve as switches for pathway crosstalk. Phosphosites with similar regulatory functions share sequence and structural properties. Phosphosites with antagonistic functions are located apart and regulated by different kinases. This study illustrates different patterns of evolutionary conservation for activating and inhibitory sites.